Manifestaciones orales en pacientes con covid-19 en la práctica odontológica: una revisión sistemática (2021)
COVID-19 is a highly contagious and potentially fatal disease; its impact on health has modified in a particular way the way dental practices are carried out, since on the one hand there is no clarity about the oral manifestations that the virus entails.